(untitled) (Sudurpaschim Spectrum, 2024)
This article explores the power of silence in Langston Hughes’ selected poems through an African American lens, reflecting the spirit of the era. It examines how Hughes’ work captures the visionary imagination and inner conflicts of Black Americans in their daily lives, particularly during the Harlem Renaissance. Drawing from his autobiography The Big Sea (1940), Hughes addresses the cultural, political, and social issues faced by Black Americans, especially in the context of white domination and exploitation. The analysis of his poem The Weary Blues highlights his reflections on these themes. The article positions Hughes as a visionary poet who anticipates a future of freedom and justice for Black people through his poetic expressions.